2,5-Dimethylphenacyl carbonates: a photoremovable protecting group for alcohols and phenols - Literak, Jaromír; Wirz, Jakob; Klán, Petr (Photochemical & photobiological sciences, 2005)
Synthesis and photochemistry of a photochemically removable protecting group for alcohols and phenols, based on the 2,5-dimethylphenacyl (DMP) chromophore, is described. DMP carbonates release the corresponding hydroxy group containing molecules in high isolated yields (>70%), with quantum yields Phi= 0.1-0.2 in methanol and Phi= 0.36-0.51 in cyclohexane. The reactions proceed predominantly by the triplet pathway via E-photoenols, the lifetimes of which of approximately 2 s or 3 ms in cyclohexane or methanol, respectively, were determined by laser flash photolysis.
Keywords: ultrafialové záření; fenoly; Photolysis; kvantová teorie; alkoholy; Carbonates; Benzene Derivatives; benzenové deriváty; lasery; molekulární struktura; Phenols; Molecular Structure; Ultraviolet Rays; uhličitany; fotolýza; Lasers; Alcohols; Quantum Theory; Photochemistry; fotochemie